2021
DOI: 10.1515/med-2021-0292
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA XIST knockdown relieves the injury of microglia cells after spinal cord injury by sponging miR-219-5p

Abstract: Long noncoding RNAs have been demonstrated to play crucial roles in the pathogenesis of spinal cord injury (SCI). In this study, we aimed to explore the roles and underlying mechanisms of lncRNA X-inactive specific transcript (XIST) in SCI progression. SCI mice model was constructed and evaluated by the Basso–Beattie–Bresnahan method. The SCI cell model was constructed by treating BV2 cells with lipopolysaccharide (LPS). The levels of XIST and miR-219-5p were determined by the reverse transcription quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…LncRNA PVT1 is believed to target miR-186-5p/CXCL13/CXCR5 axis, and is responsible for neuropathic pain caused by overactivation of astrocytes . Sponging of miR-219-5p by lncRNA XIST inhibited the viability of microglia cells, thereby affecting neuropathic pain (Zhong et al, 2021). In recent studies, antisense lncRNAs were also found to affect neuropathic pain.…”
Section: Non-coding Rnas Regulate Neuropathic Pain Via Glial Cell Act...mentioning
confidence: 98%
“…LncRNA PVT1 is believed to target miR-186-5p/CXCL13/CXCR5 axis, and is responsible for neuropathic pain caused by overactivation of astrocytes . Sponging of miR-219-5p by lncRNA XIST inhibited the viability of microglia cells, thereby affecting neuropathic pain (Zhong et al, 2021). In recent studies, antisense lncRNAs were also found to affect neuropathic pain.…”
Section: Non-coding Rnas Regulate Neuropathic Pain Via Glial Cell Act...mentioning
confidence: 98%
“…The changes in the expression of these molecules led to the decrease of apoptosis rate [ 26 ]. Similarly, Zhong et al reported that LncRNA XIST knockout can affect the expression of apoptosis-related proteins through targeting miR-219-5p, thus reducing apoptosis in spinal cord injury rat models [ 27 ]. In addition, knockdown of lncRNA-XIST has a momentous protective effect on SCI recovery by suppressing apoptosis through miR-494/PTEN/PI3K/AKT signaling axis [ 28 ].…”
Section: Role Of Lncrnas In the Pathological Process Of Spinal Cord I...mentioning
confidence: 99%
“…Recently, non-coding RNAs (ncRNAs), for example, microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), have been identified as pivotal players in SCI (Kimura et al, 2021;. Of note, the knockdown of certain lncRNAs such as TUG1, XIST, and ZFAS1 has shown a beneficial effect on SCI development through mouse as well as rat model studies (Chen Y. et al, 2021;Wu et al, 2021;Zhong et al, 2021), indicating the functional involvement and preclinical significance of these ncRNAs in SCI.…”
Section: Introductionmentioning
confidence: 99%